Active‐ion‐gated room temperature acetone gas sensing of ZnO nanowires array. Issue 6 (14th October 2022) - Guo, Junmeng; Gan, Jiahui; Ruan, Haoran; Yuan, Xiaobo; Kong, Chuiyun; Liu, Yang; Su, Meiying; Liu, Yabing; Liu, Wei; Zhang, Bao; Zhang, Yongle; Cheng, Gang; et al.
Abstract: Reducing the high operation temperature of gas sensor to room temperature (RT) have attracted intense interests for its distinct preponderances, including energy‐saving and super stability, which presents great prospects in commercial application. The exciting strategies for RT gas sensing, such as unique materials with activated surface or light activation, do not directly modulate the active ions for gas sensing, limiting the RT gas sensing performances. Here, an active‐ion‐gated strategy has been proposed for RT gas sensing with high performance and low power consumption, in which gas ions in triboelectric plasma are introduced into metal oxide semiconductor (MOS) film to act as both floating gate and active sensing ions. The active‐ion‐gated ZnO nanowires (NWs) array shows a sensitivity of 38.3% to 10 ppm acetone gas at RT, and the maximum power consumption is only 4.5 mW. At the same time, the gas sensor exhibits excellent selectivity to acetone. More importantly, the response (recovery) time of this sensor is as low as 11 s (25 s). It is found that OH − (H2 O)4 ions in plasma are the key for realizing RT gas sensing ability, and an accompanied resistive switch is also observed. It is considered that the electron transfer between OH − (H2 O)4 and ZnO NWs will forms a hydroxyl‐like intermediate state (OH*) on the top of Zn 2+, leading to the band bending of ZnO and activating the reactive O2 − ions on the oxygen vacancies. The active‐ion‐gated strategy proposed here present a novel exploration to achieving RT gas sensing performance of MOS by activating sensing properties at the scale of ions or atoms. Abstract : This paper demonstrates a novel active‐ion‐gated strategy to active the room temperature (RT) gas sensing performance of ZnO NWs by self‐powered triboelectric plasma system in ambient environment. The activated ZnO NWs shows considerable sensitivity, excellent selectivity, and rapid response to acetone gas at RT with maximum power consumption only 4.5 mW.